Comparative analysis of superovulated versus uterine-embryo synchronized recipients for embryo transfer in cynomolgus monkeys (Macaca fascicularis) - Lee, Dong-Ho; Yoon, Seung-Bin; Jo, Yu-Jin; Mo, Jun Won; Kwon, Jeongwoo; Lee, Sang Il; Kwon, Jungkee; Kim, Ji-Su (Frontiers in Veterinary Science, 2024)
IntroductionAssisted reproductive technologies (ARTs), such as intracytoplasmic sperm injection and embryo transfer, are essential for generating genetically edited monkeys. Despite their importance, ARTs face challenges in recipient selection in terms of time and the number of animals required. The potential of superovulated monkeys, commonly used as oocyte donors, to serve as surrogate mothers, remains underexplored. The study aimed to compare the efficacy of superovulated and uterine-embryo synchronized recipients of embryo transfer in cynomolgus monkeys (Macaca fascicularis).MethodsThis study involved 23 cynomolgus monkeys divided into two groups–12 superovulated recipients and 11 synchronized recipients. The evaluation criteria included measuring endometrial thickness on the day of embryo transfer and calculating pregnancy and implantation rates to compare outcomes between groups.ResultsThe study found no statistically significant differences in endometrial thickness (superovulated: 4.48 ± 1.36 mm, synchronized: 5.15 ± 1.58 mm), pregnancy rates (superovulated: 30.8%, synchronized: 41.7%), and implantation rates (superovulated: 14.3%, synchronized: 21.9%) between the groups (p > 0.05).ConclusionThe observations indicate that superovulated recipients are as effective as synchronized recipients for embryo transfer in cynomolgus monkeys. This suggests that superovulated recipients can serve as viable options, offering an efficient and practical approach to facilitate the generation of gene-edited models in this species.